Passion Plays: The Dominican Diaspora in Waddys Jáquez’s P.A.R.G.O. - Maja Horn (Studies in 20th & 21st Century Literature, 2008)
This article analyzes how the play P.A.R.G.O. (2001), written, directed, and performed by the Dominican Waddys Jáquez represents the contemporary experience of the Dominican diaspora. Jaquéz himself forms part of a new generation of diasporic artists who frequently return “home,” to the Dominican Republic, and who, unlike the previous generation of diasporic artists and writers, continue to find their most valuable audience there. This tendency towards an increasing interconnectivity between diaspora and homeland is represented and a/effectively reinforced in P.A.R.G.O. The play brings the experience of the diaspora close to home for the audience, not by compelling them to identify with the characters’ particular identities, but rather by placing center stage their ongoing negotiations and “making do” with personal and economic difficulties that define their lives both at home and abroad.
Keywords: diaspora; Dominican theatre; PARGO; P.A.R.G.O; Waddy Jáquez; Dominican diaspora; Dominican Republic; homeland